Discrimination, Affect, and Cancer Risk Factors among African Americans - Cuevas, Adolfo G. (2014)
OBJECTIVES: To examine whether stress or depressive symptoms mediated associations between perceived discrimination and multiple modifiable behavioral risk factors for cancer among 1363 African American adults. METHODS: Nonparametric bootstrapping procedures, adjusted for sociodemographics, were used to assess mediation. RESULTS: Stress and depressive symptoms each mediated associations between discrimination and current smoking, and discrimination and the total number of behavioral risk factors for cancer. Depressive symptoms also mediated the association between discrimination and overweight/obesity (p values < .05). CONCLUSIONS: Discrimination may influence certain behavioral risk factors for cancer through heightened levels of stress and depressive symptoms. Interventions to reduce cancer risk may need to address experiences of discrimination, as well as the stress and depression they engender.